E-learning platforms for boarding schools - Karimah, Fitrah (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2024)
This study examines the adoption and impact of e-learning platforms in boarding schools. Boarding schools present unique educational challenges, making them a compelling case for exploring the effectiveness of digital learning solutions. The study begins with a comprehensive needs assessment involving stakeholders such as administrators, teachers, students, and IT staff. Key areas of focus include technological infrastructure, internet accessibility, and digital literacy levels. The study then moves to the implementation phase, piloting an e-learning platform in select schools to evaluate its effectiveness. Results indicate significant challenges, including outdated infrastructure and varying levels of digital literacy. However, e-learning platforms show promise in enhancing educational outcomes by offering interactive content and improving communication. The study compares different platforms, such as Google Classroom, Moodle, and Microsoft Teams, to determine the most suitable options for these institutions. Findings suggest that while some platforms are more user-friendly, others offer robust customization and scalability, making them better suited for the specific needs of boarding schools.